If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.9 + 9y + y = -1 Combine like terms: 9y + y = 10y 0.9 + 10y = -1 Solving 0.9 + 10y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.9' to each side of the equation. 0.9 + -0.9 + 10y = -1 + -0.9 Combine like terms: 0.9 + -0.9 = 0.0 0.0 + 10y = -1 + -0.9 10y = -1 + -0.9 Combine like terms: -1 + -0.9 = -1.9 10y = -1.9 Divide each side by '10'. y = -0.19 Simplifying y = -0.19
| 12x-7=3+1-x | | -3k+5(6-k)=4(1-2k)+6 | | -10+2x=5x-31 | | 4x^3+3x^2=4X+3 | | 6+6q=11+5q | | 5(22+-2y)-2y=-10 | | -1(-4)= | | 2y-6x=5 | | 6x^2+30=0 | | 10a-15b= | | 0=-2x+4x+4 | | 152=x+x+2(2x-16) | | x*x+7x=7 | | -0.01*x+60=0 | | 3x+-y=-1 | | -3x+3=6-4x | | V+lwh= | | -0.01*x+60=25 | | x/x+7x=7 | | -3c+11A-5a-11c+9c= | | (XxX)+7x=7 | | 1+6x=4x-11 | | x+7x=7 | | fx=x^2+3 | | -0.1*x+60=25 | | 1-2x(5+x)=7 | | (x+4)(x-2)=112 | | 3u^2-75=0 | | Y^2-2y-13=0 | | 2a-5(a+1)=0 | | 3a+2a-a=24 | | x(x+5)-10=x^2-2x+4 |